Anti cancer activity of plant extracts on MDA-MB231 - Yussoff, Seri Wahyuni (2015)
Local plants of Annona squamosa L., Strobilanthes crispus, Cinnanomum iners, Premna cardifolia, Barringtonia racermosa L., Acalypha indica, Ipomoea aquatica, Gynura procumbers, Vigna unguiculata L., Piper betle L. and Piper nigrum L. were selected for their potential anti-cancer property. The leaves of plants were extracted using methanol and tested on breast cancer cell, MDA-MB-231. The MTT cytotoxicity assay has been carried out to calculate the IC50. The result shown Annona squamosa L. and Piper betle L. has potential anti cancer activity with IC50 of 500.234 μg/ml and 375.710 μg/ml respectively. Meanwhile, Piper nigrum L. was cytotoxic to Chang liver cell with IC50 of 721.770 μg/ml.